Peran Istiḥsān Dalam Dinamisasi Pemikiran Hukum Ekonomi Syariah - Alimatul Farida; Abu Yasid; Muhammad Lathoif Ghozali (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The rapid growth of generations, science and technology raises a variety of new problems that are not only solved by the source of the law of the Koran and hadith. Istiḥsān is a way of finding Islamic law which is used as a postulate infiqh Hanafi, although its existence is still being debated among fiqh scholars. This paper aims to examine the roleIstiḥsānas a method for discovering Islamic law, particularly in the field of sharia economics. The research approach uses qualitative research with the type of document or text study research, namely, a series of activities related to gathering information relevant to the topic of rolesistiḥsān, read, record and process research materials. The research findings in this paper show thatIstiḥsān is an important option in determining sharia economic law, such as buying and selling contractsSalam, al-istiṣnāʿ, muʿatāh, online shop and vending machine which can currently be solved by methodIstiḥsān,Besides that legal provisions that apply with a basic purposeIstiḥsānis eliminatingmadhorot and reach maṣlāḥa.